2022
DOI: 10.1002/ccr3.5931
|View full text |Cite
|
Sign up to set email alerts
|

Cervical epidural abscess due to implantation of a spinal cord stimulation lead

Abstract: Spinal cord stimulation (SCS) for intractable pain syndromes has become a pillar of modern pain management. Common complications include lead migration, implant infection, cerebral spinal fluid leak, and lead fracture. Spinal epidural abscess due to spinal cord stimulator implantation is a very rare occurrence with only two cases reported in the literature so far. We present an illustrative case and discuss the pathophysiology and best clinical management for this very rate entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…If an infection is suspected, practitioners should obtain appropriate cultures and perform imaging studies to confirm the diagnosis. Treatment typically involves the removal of infected hardware and antibiotic administration [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If an infection is suspected, practitioners should obtain appropriate cultures and perform imaging studies to confirm the diagnosis. Treatment typically involves the removal of infected hardware and antibiotic administration [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding SCS-related infections, another study reported a rare cervical epidural abscess due to spinal cord stimulation lead implantation. The study highlighted that spinal epidural abscess is rare, with only two cases documented in the literature [ 4 ].…”
Section: Introductionmentioning
confidence: 99%